Export Function of Cocoa Production, Exchange Rate Volatility and Prices in Nigeria - Alori, Alaba David; Kutu, Adebayo Augustine (Journal of Economics and Behavioral Studies, 2019)
This study examined the export function of cocoa production and determined the impact of exchange rates and price volatility on the exportation of cocoa in Nigeria. The Phillips-Perron (PP) and Augmented Dickey-Fuller (ADF) unit root tests, Ordinary Least Square (OLS) and Structural Vector Autoregressive (SVAR) methodologies were employed to analyse the time series data that spanning from 1970:01 to 2016:12. The PP and ADF unit root tests findings indicated that none of the variables was stationary at levels (I (0)) however, after the first difference I (1) they became stationary. At 5%, the OLS results showed that all the variables were statistically significant in analysing the effects of exchange rates and price volatility on the value of cocoa production in Nigeria. The price of cocoa in the international market and the value of exchange rates play a significant role in cocoa exports growth in Nigeria. Further, findings from the SVAR showed that an increase in the price of cocoa would increase cocoa production and cocoa export growth in Nigeria, while the exchange rate volatility would affect cocoa export growth in Nigeria. The result further revealed that the shocks to exchange rate accounted for the greater volatility (positively significant for the entire period) to the value of cocoa exported, as against other variables in the model. Based on those findings, the paper, therefore, recommends that there should be a free exchange rate market determination, in order to enhance the export growth and increase cocoa output in Nigeria.